Psychotropic territories in the center of Porto Alegre city, Rio Grande do Sul, Brazil - Raupp, Luciane; Adorno, Rubens de Camargo Ferreira (Saúde e Sociedade, 2015)
This article is the result of research based on the human and social sciences aiming to understand the everyday life of crack users in the center of Porto Alegre city. Participant observations and informal interviews were conducted to characterize users, the forms and effects of drug use, the disease and health process in their daily life and their survival strategies. The daily life of the place studied is connected to the history of degradation of the city's central area, currently marked by attempts to control and arrange the urban space. Most users were males, lived on the streets, had transmitted diseases and a compulsive pattern of crack use linked to the economic and social precariousness of their lives, although crack users have been observed who are capable of controlling their relationship with the drug, employing strategies of self-control and survival.